Improving a Simple Financial Management System for MSMEs in the Digital Era - Solihat, Asri; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah; Dahlena, Alni (Indonesian Journal of Community Empowerment (IJCE), 2024)
The fact that digitalization still exists in the field can help MSMEs improve the efficiency of their financial management. Strengthening understanding of digitalization issues plays a crucial role in helping MSMEs improve their financial management efficiency. This community service activity involved lectures, collaboration, and mentoring to directly implement a simple financial management system for MSMEs in Garut. The activities involved lectures, collaboration, and mentoring to directly implement a simple financial management system for MSMEs in Garut. The results of this activity interpreted the simple yet effective digital-based financial management system. The training materials were designed based on the needs of MSMEs who desire a system that is easy, cost-effective, and can be directly applied to daily operations. This increased participants' understanding of basic financial management concepts.